THE OPTIMIZING THE ROLE OF THE PATROL UNIT SUKOHARJO POLICE IN PREVENTING THE CRIME OF THEFT AND VIOLENCE (CURAS) - AMIRUL FADEL KURNIYANTO Tugas (Police Studies Review, 2022)
The author's final project raises the issue of "How To Optimize The Role Of The Satsamapta Patrol Unit Sukoharjo Police In Preventing The Crime Of Theft And Violence (curas)?". This final project aims to identify how the Response Team patrols to prevent the crime of stealing have occurred so far. In this study using a qualitative approach with the type of field research research by conducting observations, interviewing resource persons and document studies. In addition, the data used is also obtained from document data and reports. This study uses 4m and 6m management theory as well as the concepts of legislation and the concept of the patrol itself. Satsamapta Polres Sukoharjo in matters concerning cases of criminal acts of robbery is quite rare, but there are still some reports that come in. The efforts of the Samapta Patrol Unit at the Sukoharjo Police have not been carried out optimally. One of them is human resources that are still inadequate in carrying out the patrols of the Rapid Response Team itself. Besides that, the lack of complete infrastructure facilities such as patrol motorbikes is still very minimal so that the implementation of Patrol by the Quick Reaction Team in the implementation of the crime of stealing has not run optimally. Efforts are needed to increase the competence and number of members to support the success of patrol activities. It is also necessary to conduct outreach and socialization to the community so that it can maintain good relations with the community in order to support the implementation of Patrol by the Quick Reaction Team so that the implementation of the Patrol of the Quick Reaction Team in preventing criminal acts of robbery in the Sukoharjo Police area can run optimally.